THE INFLUENCE OF JOB SATISFACTION AND WORK LOYALTY ON THE PRODUCTIVITY OF EMPLOYEES AT THE AGAM REGENCY AGRICULTURE SERVICE - Dasril, Mience; Rusdi, Rusdi; Aima, M. Havidz; Lusiana, Lusiana (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study aims to analyze the influence of job satisfaction and loyalty on employee productivity at the Agam Regency Agriculture Office. Job satisfaction and loyalty are two important factors in human resource management that are believed to contribute to achieving optimal employee performance. This study uses a quantitative approach with an associative research type. The population in this study were all employees of the Agam Regency Agriculture Office, with a sample of 80 people selected through proportional random sampling technique. Data collection was carried out through distributing questionnaires with a Likert scale, and the data were analyzed using multiple linear regression. The results of the study indicate that partially, job satisfaction has a positive and significant effect on employee productivity. Similarly, loyalty has a positive and significant effect on productivity. Simultaneously, both variables have a significant influence on employee productivity. These findings confirm that efforts to increase work productivity in government agencies can be achieved through continuous improvement of employee job satisfaction and loyalty.